Deployment of an easy-to-use VOIP phone under a Linux-based thin client - Despi, Mark William C. (2006)
VoIP (Voice-over-IP) is quickly gaining in popularity as a method of making cheap and efficient voice calls. However, most VoIP phones are cumbersome and difficult to use. Thin Clients offer low-cost and easily manageable alternatives to individual computers in the workplace,especially for users who do not need a lot of computing power. Despite this, thin clients tend to have limited functionality built into them. This research implemented a "zero-configuration" VoIP phone over a low-cost, low power consumption, Linux-based thin client. The research used readily available software modified and configured for optimum simplicity and ease of use. The thin client itself was assembled from off-the-shelf hardware, and a custom operating system, based on Linux, was installed on it. The operating system's design goals were minimum footprint, simplicity, robustness and speed. However, the limitations of the current version of Microsoft's Remote Desktop Protocol prevented the research from completing its design goal of implementing a full functional VoIP phone. Bidirectional audio was not available, so the transmission of voice from client server could not be achieved.